Thyroid function and gallstone disease: is there an association? - Nair, Kharishma P.; S., Siddartha Gowthaman; S., Vinoth; Manickam, Ramanathan (International Surgery Journal, 2021)
Gallstone disease, amounts to a significant amount of disease burden to the medical society, more commonly encountered in the West. Various predisposing factors are associated with the development of cholelithiasis, namely age, gender, dietary food habits and haemolytic conditions, but whether or not thyroid dysfunction is a causative factor, till date, is a subject of dispute. Gallstones can be classified into cholesterol stones and pigment stones which are black or brown (with cholesterol) in colour. Thyroid hormones are said to have a direct effect on the sphincter of oddi, thereby aiding in biliary emptying. They also alter the lipid metabolism which is said to cause supersaturation of cholesterol in bile, and hence result in the formation of cholesterol stones. Several studies have tried to establish this hypothesis and have concluded with diversified results. This review article throws light into the concept of the association between thyroid dysfunction and formation of gallstones by evaluating several articles through a systematic approach in order to arrive at a better consensus.